2007
DOI: 10.1128/jvi.01502-07
|View full text |Cite
|
Sign up to set email alerts
|

Prion Strain- and Species-Dependent Effects of Antiprion Molecules in Primary Neuronal Cultures

Abstract: Transmissible spongiform encephalopathies (TSE) arise as a consequence of infection of the central nervous system by prions and are incurable. To date, most antiprion compounds identified by in vitro screening failed to exhibit therapeutic activity in animals, thus calling for new assays that could more accurately predict their in vivo potency. Primary nerve cell cultures are routinely used to assess neurotoxicity of chemical compounds. Here, we report that prion strains from different species can propagate in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 57 publications
(58 reference statements)
3
60
0
Order By: Relevance
“…In the previous reports using prion-infected primary cultured neurons, antimitotics were used throughout the culture period to suppress the growth of astrocytes (Carimalo et al, 2005;Cronier et al, 2007;Hannaoui et al, 2013), and some of them confirmed the neuronal predominance with astrocytes at 4 -5 % of the cellular composition at an early stage (Cronier et al, 2004). However, antimitotics will be harmful to neurons depending on concentrations and the period of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In the previous reports using prion-infected primary cultured neurons, antimitotics were used throughout the culture period to suppress the growth of astrocytes (Carimalo et al, 2005;Cronier et al, 2007;Hannaoui et al, 2013), and some of them confirmed the neuronal predominance with astrocytes at 4 -5 % of the cellular composition at an early stage (Cronier et al, 2004). However, antimitotics will be harmful to neurons depending on concentrations and the period of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Some transgenic lines have been established by a gene replacement method (for review [44]). PrP sequence identity between the transgenic host and donor usually lead to an enhanced susceptibility to TSE as compared to wild-type [58,127] mice. Moreover, in various instances, the TSE agent original properties, in particular PrP Sc molecular profile, appeared to be essentially maintained in the infected transgenic host (see also Sect.…”
Section: Influence Of the Prp Genementioning
confidence: 99%
“…Primary cultures of cerebellar granule neurons (CGN) were established as previously described (Cronier et al, 2007). Briefly, CGN cells were extracted from 5-or 6-d-old PrP knockout mice Zurich I (Büeler et al, 1992) by enzymatic and mechanical dissociation.…”
Section: Mouse Cerebellar Granule Neuronsmentioning
confidence: 99%